The role of institutional policies in the sustainability of institutional repositories in Africa: A reflection from Ghana - Imoro, Osman; Saurombe, Nampombe (Journal of information science, 2024)
Institutional repositories (IRs) are increasingly gaining prominence among African academic institutions, and Ghana is no exception. This can largely be attributed to the enduring value of hosting research outputs from institutional and individual depositors. Despite its increasing adoption, there is a growing concern about the sustainability of open access IRs, particularly in Africa. However, most of these factors that threaten the sustainability of IRs on the continent can be mitigated by enacting comprehensive institutional policies. Thus, this study sought to examine the role of institutional policies in the sustainability of IRs in Ghana. A total of 830 respondents comprised of IR managers, library staff, postgraduate students, lecturers and university librarians (management) from five public universities in Ghana took part in this study. Questionnaires, semi-structured interviews and document analysis were the main instruments used for data collection. The study yielded an overall response rate of 92.8%. The study findings revealed that public universities in Ghana have institutional IR policies that guide the operation, usage and management of their IRs. However, these policies were persuasive in nature and mainly focused on content submission and generation issues. The study underscored the IR policy’s importance in addressing content generation, awareness, advocacy and copyright restriction challenges. The study recommends the necessity of IR policies to focus on other factors such as technical requirements, expertise and others to ensure the sustainability of these repositories.